What’s In Between? The Unarchived and Unarchivable Space of Found-Footage Cinema - Winand, Annaëlle (Archivaria)

(untitled) (Association of Canadian Archivists, 2023)
Between archives, as documentary by-products of human activity retained for their long-term value, and the archive, as a concept used outside of the discourse of professional archivists, there is a semantic, conceptual, and theoretical gap. However, this interval is particularly fertile. In this space, non-traditional archives users such as found-footage filmmakers find inspiration. Through the narratives of their work, they show what is not always visible in archives. Their artworks confront us with unarchived and unarchivable dimensions (what is not archived and what cannot be archived), constituent of how archives are created. In studying the archives that are part of found-footage works through an archival usage framework (exploitation), three main cat- egories of the unarchived and the unarchivable emerge: absence, which is linked to gaps, fragments, and incompleteness; the forbidden, which manifests in archives as material traces; and the invisible, which is not shown. These three categories have to do with an unconceived (impensé) state – a state of the archival field reflecting the intentional or unintentional inconceivability or omission of some of its theoretical or practical aspects. By investing in the unconceived – in other words, by studying archival science from practices on the margins – it is possible to renew ideas and discourses inside the discipline.